The Effectiveness of Central Bank Interventions During the First Phase of the Subprime Crisis - Hesse, Heiko (IMF Working Papers; Working Paper ;, 2009)
This paper provides evidence that central bank interventions had a statistically significant impact on easing stress in unsecured interbank markets during the first phase of the subprime crisis which began in July 2007. Extraordinary liquidity provisions, such as the Term Auction Facility by the Federal Reserve, are analyzed. First a decomposition of the Libor-OIS spread indicates that credit premia increased in importance as the crisis deepened. Second, using Markov switching models, central bank operations are then graphically associated with reductions in term funding stress. Finally, bivariate VAR and GARCH models are adopted to econometrically quantified these impacts. While helpful in compressing Libor spreads, the economic magnitudes of central interventions have overall not been very large.